Unsaid thoughts: Thinking in the absence of verbal logical connectives - Lobina, David J.; Demestre, Josep; García-Albea, José E.; Guasch, Marc (Frontiers in Psychology, 2022)
Combining two thoughts into a compound mental representation is a central feature of our verbal and non-verbal logical abilities. We here approach this issue by focusing on the contingency that while natural languages have typically lexicalised only two of the possible sixteen binary connectives from formal logic to express compound thoughts —namely, the coordinators and and or— some of the remainder appear to be entertainable in a non-verbal, conceptual representational system —a language of thought— and this suggests a theoretical split between the “lexicalisation” of the connectives and the “learnability” of invented words corresponding to unlexicalised connectives. In a visual world experiment aimed at tracking comprehension related as well as reasoning-related aspects of the capacity to represent compound thoughts, we found that participants are capable of learning and interpreting a made-up word standing for logic’s NAND operator, a result that indicates that unlexicalised logical connectives are not only conceptually available, but can also be mapped onto new words.